Reducing unwanted adolescent pregnancies in Kenya: A policy brief with evidence-based options (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Adolescent pregnancy is a global health issue that affects millions of young girls and their families.According to the World Health Organization, approximately 16 million adolescents aged 15-19years give birth annually, representing 11% of all births worldwide. Most of these pregnancies occurin low- and middle-income countries (LMIC), especially in Sub-Saharan Africa. The burden ofadolescent pregnancy in Kenya is 15% of girls aged 15-19 years, with 2.7 % of adolescents aged15 years having ever been pregnant. Unintended pregnancies among adolescents in Kenyaaccount for most maternal morbidity and mortality cases from abortions. Pregnant adolescents areat an increased risk of pregnancy and childbirth complications, unsafe abortion, violence fromintimate partners, HIV/AIDS, and other sexually transmitted infections. Furthermore, infants born toadolescent mothers have higher probability of mortality and exposure to life-threatening conditions.This policy brief reviews and analyses the factors associated with unintended adolescentpregnancies in Kenya and identifies evidence-based interventions that can be applied in the localcontext. It argues that a multisectoral approach involving education, contraception, and incentivesis needed to address adolescent pregnancies. In conclusion, more research is needed to tailorthese interventions to the local Kenyan context while analyzing the availability and mobilization ofresources.